2011
DOI: 10.1007/s10461-011-0095-8
|View full text |Cite
|
Sign up to set email alerts
|

OPRM1 and Diagnosis-Related Posttraumatic Stress Disorder in Binge-Drinking Patients Living with HIV

Abstract: Posttraumatic stress disorder (PTSD) has been linked to numerous negative outcomes in persons living with HIV (PLH) and there is evidence that PTSD symptoms may play a role in maintaining alcohol use problems. The opioid receptor mu-1 (OPRM1) gene may play a role in both PTSD and alcohol use. We examined the association between PTSD and drinking motives as well as variation in the OPRM1 as a predictor of both PTSD and drinking motives in a sample of 201 PLH reporting recent binge drinking. Self-reported PTSD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
0
17
1
Order By: Relevance
“…Our results differ from those of many studies that have observed such a pathway (Goldstein et al, 2010;Grayson & Nolen-Hoeksema, 2005;Nugent et al, 2012;Simpson, 2003;Simpson et al, 2014). In addition, we did not find any gender differences when the model was tested separately for males and females.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results differ from those of many studies that have observed such a pathway (Goldstein et al, 2010;Grayson & Nolen-Hoeksema, 2005;Nugent et al, 2012;Simpson, 2003;Simpson et al, 2014). In addition, we did not find any gender differences when the model was tested separately for males and females.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, many of the studies measured childhood abuse or neglect any time before age 18 (Goldstein et al, 2010;Grayson & Nolen-Hoeksema, 2005;Nugent et al, 2012;Simpson, 2003;Simpson et al, 2014), whereas we measured trauma occurring much earlier. The earlier exposure to trauma would be expected to have a greater effect on developing emotion regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other studies suggest that a polymorphism in the OPRM1 gene (opioid receptor μ–1) is associated with less severe PTSD symptoms (138). Regarding specific PTSD-related symptoms, κ opioid receptor availability in the amygdala-anterior cingulate cortex-ventral striatal circuit mediates the expression of dysphoria where lower κ opioid receptor is associated with greater severity of trauma-related loss symptoms (139).…”
Section: Pharmacotherapy Approaches To Fear- and Anxiety-related Disomentioning
confidence: 82%
“…All behavioral testing was videotaped with a Sony Digital Video Camera with NightShot feature for recording in low light. The time spent sniffing the stimulus mouse in the cylinder was measured, as it has been previously shown to be a direct and sensitive measure of sociability (Moy et al, 2007). All testing was conducted in dim light conditions (1-2 lux).…”
Section: Methodsmentioning
confidence: 99%